Modeling resource basis for social and economic development strategies: Water resource case - Kosolapova, Natalia A.; Matveeva, Ludmila G.; Nikitaeva, Anastasia Y.; Molapisi, Lesego (Journal of hydrology (Amsterdam), 2017)
•A new approach to water resource distribution on the basis of the Game Theory.•The tools for strategic water management of river basins.•Achieving a balance of interests for participants in the water management complex.•A toolkit for supporting decision-making for the allocation of water resources.•The connection between rational water supply and economic indicators of regions. The article substantiates that the effectiveness of implementing socio-economic development strategies is to a large extent determined by the adequate provision of basic resources. The key role of water resources in economic strategic development is empirically illustrated. The article demonstrates the practicability of strategic management of water resources based on the principle of a combination of river basin management approaches and the consideration of regional development strategies. The Game Theory technique was used to develop economic and mathematical tools for supporting decision-making in meeting the needs of regional consumers under water balance deficit conditions. The choice of methods was determined from two positions: the methods should allow for the possibility of multi-variant solutions for the selection of optimal options for the distribution of limited water resources between different consumers; the methods should be orientated on the maximum possible harmonization of multidirectional and multi-scale interests of the subjects in the water management system of the different regions (including the state) in order to achieve a balance. The approbation of developing a toolkit for the example of the regions located in the Don and Kuban river basins resulted in the appropriate selection of priority regions for the allocation of water resources in terms of strategic management as well as the determination of measures of ensuring the sustainable use of the river basins under consideration. The proposed tools can be used for coordinating decisions on the water supply of regional economic systems with actual and projected indicators of socio-economic development of the respective regions for a strategic perspective.